Studies on the Total Synthesis of Antibiotic Macrolactin S: A Conventional Approach for the Synthesis of the C1–C9 and C10–C24 Fragments - Sayini, Ramakrishna; Srihari, Pabbaraja (Synthesis, 2018)
The C1–C9 and C10–C24 segments of the 24-membered polyene macrolide macrolactin S were synthesized by routes involving an epoxide-ring-opening reaction, an Ohira–Bestmann alkyne formation, a chelation-controlled nucleophilic addition reaction, and a Still–Gennari olefination as key steps. A chiron approach , starting from readily available glucose diacetonide, was used to synthesize a key intermediate, and a convergent approach was adopted for the synthesis of the key C10–C24 fragment.
Keywords: macrolides; polyenes; antibiotics; total synthesis; Julia olefination; Ohira–Bestmann reaction